Pasar Senen : Reorganisasi Pasar Tahun 1966 - 1993 - Annissa Ferissa (Historia Madania: Jurnal Ilmu Sejarah, 2018)
Pasar Senen is one of the oldest markets in Jakarta and still keeping their existences more than 250 centuries, starting from Dutch era, Japanese Occupation era, until the Independence of Indonesia. The main problem in this article is a study on the development of Pasar Senen from 1966 until 1993. The method used is the historical method. There are heuristic, critics, interpretation, and historiography. The result of this thesis indicated that: Firstly, Pasar Senen’s still growing because their supported by a modern management and infranstructure. Secondly, Pasar Senen has two organizing managemens, whicht are PT Pembangunan Jaya and PD Pasar Jaya. Thirdly, There managements have changed Pasar Senen from traditional market became modern market. The last result is the evidence that Pasar Senen is to meet the needs of society as consumers, and maintain the existence with keep progresin the capital city Jakarta. Keywords : Trade, Market, Traditional, Policy